Clinical psychiatry teaching and learning goes virtual / Nurul Azreen Hashim, Nor Jannah Nasution Raduan & Salmi Razali - Hashim, Nurul Azreen; Nasution Raduan, Nor Jannah; Razali, Salmi (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
COVID-19 crisis has caused severe disruption to teaching and learning activities. One of the recommended steps to prevent further spread of the illness is by physical distancing practice. Therefore, the current model of teaching and learning in psychiatry posting for medical undergraduates in Year 4 and Year 5 need to be enhanced by integrating virtual learning with traditional face-to-face methods. The ordinary bedside teaching and interview techniques were mostly converted into role plays, simulated patients, and recorded interview sessions with real patients via video conferences. Only a few learning sessions with patients were carried in-person, and adherence to strict protocols is compulsory. Case presentations and seminars were conducted via online platforms such as Microsoft Teams, Zoom, Google Meet and Skype. Logbook assessments and end posting evaluations were done through Google Form and viva voce through video conferences. Feedback from students was collected using Google Forms. Overall, students' responses had been positive regarding this new approach in psychiatry teaching and learning. In conclusion, this COVID-19 crisis has unfolded the potential of collaborative pedagogical practice to a virtual teaching and learning environment in psychiatry.